2017
DOI: 10.18203/2349-2902.isj20175100
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of ropivacaine alone versus ropivacaine with dexamethasone in supraclavicular brachial plexus block

Abstract: INTRODUCTIONPain is an unpleasant effect associated with significant psychological and physiological changes during surgery and post-operative period. Regional anaesthetic techniques have specific advantages either for standalone anaesthesia or as analgesic supplements for intraoperative and postoperative care. Brachial plexus block is often used either as an adjuvant to general anesthesia (GA) or as a sole anesthesia modality. Brachial plexus blockade for ambulatory upper-limb surgery can significantly reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The full‐text manuscripts of the remaining 312 studies were assessed. After including studies from hand searches and revision of search, we identified a total of 100 studies for inclusion in this network meta‐analysis [32–131]. The study flow chart is in online Supporting Information Figure S1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The full‐text manuscripts of the remaining 312 studies were assessed. After including studies from hand searches and revision of search, we identified a total of 100 studies for inclusion in this network meta‐analysis [32–131]. The study flow chart is in online Supporting Information Figure S1.…”
Section: Resultsmentioning
confidence: 99%
“…The network geometry for our two main outcomes was as follows. Eighty‐five trials with 5134 patients examined sensory block duration [33–39, 41–43, 45, 47, 48, 52, 55–59, 61, 63, 65, 67, 68, 70, 71, 73–111, 113–131] (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations